#TITLE_ALTERNATIVE# - RENDY RESTU KURNIA (NIM : 10206002); Pembimbing : Dr. Eng. Alamta Singarimbun,
Gravity method is one of the geophysical exploration methods which can describe the form of subsurface structures. Gravity data processing is done by taking into account all correction factors to obtain the Bouguer anomaly, which are reduced by regional anomaly to obtain the residual anomaly. The next process is to create 2-D modeling of variation in the density of rocks below the surface. Modeling carried out using MATLAB software with modeling approaches Talwani 2-D Polygons. Modeling of the gravity method is expected to give shape and depth information from a geothermal reservoir in the area of X. Modeling results are the density value of caprock layer 2.98 gr/cm3, reservoir 2.3 gr/cm3, and bedrock 3.03 gr/cm3. Reservoir is estimated to have a thickness of 1600 m at depths between 700-2300 meters.